Flora, conservation value and ecological potential of the cer boundary channel (Šabac, Serbia) - Damnjanović Bojan (Proceedings of the International Symposium on Analytical and Environmental Problems, 2022)
Channels can represent significant areas of plant diversity in urban ecosystems. The aim of this paper is to determine recent flora of aquatic macrophytes as well as determining the conservation values and ecological potential based on the macrophyte in one part of the Cer boundary channel. Field research conducted during the summer of 2020 of total lenghth of 5km upstream from the estuary. Macrophute data was collected according to the standard UKTAG LEAFPACS method. A total of 13 macrophyte species were recorded out of which three species are on the list of endangered and protected species. The ecological potential of the researched part of the channel flow was graded as good and better. Based on the results can conclude that the Cer boundary channel represents an optimal habitat for the development of aquatic vegetation and thus other hydrobionts, as well as for the development of other rare and endangered types of macrophytes. Results confirm the fact that artificial water bodies can play a significant role in biodiversity conservation in urban ecosystems.